2012
DOI: 10.1063/1.4720503
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen scrambling in ethane induced by intense laser fields: Statistical analysis of coincidence events

Abstract: Two-body Coulomb explosion processes of ethane (CH(3)CH(3)) and its isotopomers (CD(3)CD(3) and CH(3)CD(3)) induced by an intense laser field (800 nm, 1.0 × 10(14) W/cm(2)) with three different pulse durations (40 fs, 80 fs, and 120 fs) are investigated by a coincidence momentum imaging method. On the basis of statistical treatment of the coincidence data, the contributions from false coincidence events are estimated and the relative yields of the decomposition pathways are determined with sufficiently small u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
17
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 23 publications
4
17
1
Order By: Relevance
“…2a, which peaks at 4.7 eV. This peak value is larger than the previous results of~4.0 and 4.3 eV obtained in strong laser field ionization 28,29 . This is probably caused by the drastic modification of the dication PES by the intense laser interaction, for example, suppressing the dissociation barrier towards the H 3 + fragments and thus making the original KER smaller.…”
Section: Resultscontrasting
confidence: 63%
“…2a, which peaks at 4.7 eV. This peak value is larger than the previous results of~4.0 and 4.3 eV obtained in strong laser field ionization 28,29 . This is probably caused by the drastic modification of the dication PES by the intense laser interaction, for example, suppressing the dissociation barrier towards the H 3 + fragments and thus making the original KER smaller.…”
Section: Resultscontrasting
confidence: 63%
“…Despite this, we have listed here only selected studies performed from 2004 to data on Coulomb explosion of isolated large molecules initiated by femtosecond laser pulses. The family of molecules include aliphatic and [52,125,[141][142][143][144][145][146][147][148][149][150][151][152][153][154][155][156][157][158][159] aromatic hydrocarbons [92,[160][161][162], halogenated molecules [33,42,[163][164][165][166][167][168][169][170][171][172][173][174][175][176] and alcohols [49,51,53,155,[177][178]…”
Section: Coulomb Explosionmentioning
confidence: 99%
“…Recently, we interpreted the mechanism of H 3 + formation from dication of methanol theoretically as a unimolecular decomposition process in which a long-lived neutral moiety of H 2 , formed within a dication molecule, abstracts a proton in the other moiety having the charge of +2 11 . Through a series of our studies on the formation of H 3 + from hydrocarbon molecules by the irradiation of ultrashort intense laser pulses 7,10,[12][13][14] , we showed that the hydrocarbon dications from which H 3 + is ejected are all long lived, and that their lifetimes are comparable to or longer than a period of the overall rotation of the dications. These findings mean that the intramolecular vibrational-energy redistribution proceeds to a large extent within the energized dications prior to the ejection of H 3 + .…”
mentioning
confidence: 98%